2017
DOI: 10.1021/acsami.7b07615
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Grown S Nanosheets on Cu Foam: An Ultrahigh Electroactive Cathode for Room-Temperature Na–S Batteries

Abstract: Room-temperature sodium-sulfur batteries are competitive candidates for large-scale stationary energy storage because of their low price and high theoretical capacity. Herein, pure S nanosheet cathodes can be grown in situ on three-dimensional Cu foam substrate with the condensation between binary polymeric binders, serving as a model system to investigate the formation and electrochemical mechanism of unique S nanosheets on the Cu current collectors. On the basis of the confirmed conversion reactions to NaS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 29 publications
1
73
0
1
Order By: Relevance
“…[37] Zhang et al used nanocellulose to successfully improve the film forming property of polyaniline (PANI) and as-prepared nanocellulose-based PANI composites film with core-shell structure showed high contrast ratio and coloration efficiency in ECDs. [38] These pioneer works inspire us to construct uniform CNCs/viologen composite films and make use of them to design a novel viologen-based ECDs. To the best of our knowledge, this is the first time to report the preparation of CNCs/viologen composite-based ECDs with an organic solvent-free process.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Zhang et al used nanocellulose to successfully improve the film forming property of polyaniline (PANI) and as-prepared nanocellulose-based PANI composites film with core-shell structure showed high contrast ratio and coloration efficiency in ECDs. [38] These pioneer works inspire us to construct uniform CNCs/viologen composite films and make use of them to design a novel viologen-based ECDs. To the best of our knowledge, this is the first time to report the preparation of CNCs/viologen composite-based ECDs with an organic solvent-free process.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, room-temperature Na-S batteries have attracted much attention because of their high theoretical specific capacity (1675 mAh g −1 ) and energy density (1274 Wh kg −1 ) as well as abundant Na and S resources in the Earth's crust. [10] Finally, sodium polysulfides generated in the multistep reaction have high reactivity and solubility and are easy to diffuse to the sodium anode, resulting in serious "shuttle effect" that leads to a significant reduction in capacity. [8,9] Second, Na-S batteries have a higher volume expansion than lithium-sulfur batteries (LSBs), which makes the cathode structure of Na-S batteries prone to collapse.…”
mentioning
confidence: 99%
“…As illustrated in Figure f, Zhang et al. also confirmed the polar–polar interactions between Cu foam and S . The Cu foam is polarized with the formation of CuS and Cu 2 S during preparation of the S electrode.…”
Section: Sulfur Cathodes For Room‐temperature Na‐s Batteriesmentioning
confidence: 74%
“…The Cu foam is polarized with the formation of CuS and Cu 2 S during preparation of the S electrode. The polarized Cu foam showed high sulfur affinity and was expected to immobilize the produced polysulfide, leading to reduced shuttle phenomenon . Recently, this research group also reported on a new S host consisting of ≈10 wt % transition metal (M=Fe, Cu, and Ni) nanoclusters deposited on hollow carbon nanospheres.…”
Section: Sulfur Cathodes For Room‐temperature Na‐s Batteriesmentioning
confidence: 99%